1995
DOI: 10.1113/jphysiol.1995.sp020831
|View full text |Cite
|
Sign up to set email alerts
|

The effect of osmolality and carbohydrate content on the rate of gastric emptying of liquids in man.

Abstract: 1. The effect of osmolality and carbohydrate content on the rate of gastric emptying was assessed by using the double sampling gastric aspiration technique to measure the rate of gastric emptying of isoenergetic and isosmotic solutions of glucose and glucose polymer. Six healthy male subjects were each studied on four separate occasions using a test drink volume of 600 ml.2. The half-emptying time (t1, mean + S.E.M.) for a dilute (40 g 1-1) solution of glucose (LG, 230 mosmol kg-') was 17 + 1 min. This was gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
139
1
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(149 citation statements)
references
References 27 publications
6
139
1
3
Order By: Relevance
“…This makes it difficult to estimate reductions in total extracellular fluid volume, but, if the reduction in total extracellular fluid was similar to the decrease in plasma 0 206 171 620 198 480 307 175 36 2 265 163 493 196 473 327 191 48 5 247 170 568 284 426 246 162 58 10 181 132 482 198 465 267 189 59 volume, this equates to a decrease in extracellular fluid of approximately 384 ml. It would require approximately 700 ml of free water to dilute the 10 % glucose solution to isotonicity, but it is likely that a significant amount of hypertonic fluid remained in the gastrointestinal tract at the end of the 60 min measurement period (21,31) . It can, therefore, be concluded that the majority of water secreted into the small intestine following ingestion of hypertonic solutions is probably derived from the extracellular fluid.…”
Section: Discussionmentioning
confidence: 99%
“…This makes it difficult to estimate reductions in total extracellular fluid volume, but, if the reduction in total extracellular fluid was similar to the decrease in plasma 0 206 171 620 198 480 307 175 36 2 265 163 493 196 473 327 191 48 5 247 170 568 284 426 246 162 58 10 181 132 482 198 465 267 189 59 volume, this equates to a decrease in extracellular fluid of approximately 384 ml. It would require approximately 700 ml of free water to dilute the 10 % glucose solution to isotonicity, but it is likely that a significant amount of hypertonic fluid remained in the gastrointestinal tract at the end of the 60 min measurement period (21,31) . It can, therefore, be concluded that the majority of water secreted into the small intestine following ingestion of hypertonic solutions is probably derived from the extracellular fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Ingestion of pickle juice concomitantly with large amounts of hypotonic beverages likely would increase the rate of stomach emptying. 35 However, hypotonic fluids require at least 13 minutes to leave the stomach 36 ; thus, even with large amounts of hypotonic fluid ingested in addition to pickle juice, it is unlikely that large amounts of sodium can be absorbed in the time frame described to alleviate an EAMC. 10 …”
Section: Discussionmentioning
confidence: 99%
“…The delayed increase in plasma Na þ content in the 0-and 1-bolus conditions was likely due to a smaller volume of fluid in the stomach. Gastric emptying is delayed by small stomach volumes, 27,28 vigorous exercise, 29,30 high osmolality, 31 and low pH of ingested beverages. 32 In our study, the gastric-emptying rates were likely low for all conditions due to the small volumes ingested and vigorous exercise.…”
mentioning
confidence: 99%